Investigation of the Effect of Roof Color on the Energy Use of a Selected House in Amman, Jordan - Alrwashdeh, Saad S.; Qadourah, Jenan Abu; Al-Falahat, Ala’a M. (Frontiers in Mechanical Engineering, 2022)
Energy consumption in the buildings sector is considered one of the most important sources of energy consumption in Jordan, as the reason for this is due to the traditional building pattern and the buildings’ lack of various energy saving and rationalization systems. The development of the buildings sector in terms of the capacity of buildings to save and produce energy is one of the most important reasons that lead to saving energy consumption at the national level in Jordan. In this study, the effect of paint colors on the roofs of buildings was studied by studying three different colors, which are blue, white, and black, where it was confirmed that the best colors in energy conservation is black, and white is the opposite of it, which is considered the worst in energy conservation.